Temperature Regime in Low-Head Earth Dams in Central Yakutiaa (Temperaturnii Regim Nizkonaporn'k Zemlyan' kh Plotin v Usloviyakh Shentral'nor Yakutii) - Chzhan ,R V (1977)
The Institute of Permafrost Studies of the Siberian Department of the USSR Academy of Sciences carried out studies of the process of formation of the heat regime of catchwork and storage earth dams applicable to the climatic and engineering-geocryological conditions of the Tatta River valley where, to solve the water supply problem in Alekseyevskiy and Churapchinskiy regions of the Yakut USSR using water from the Amga River, a series of earth dams was planned for construction. The basic results of the thermal engineering forecasts made are given here. (Author) Trans. of mono. Geokriologicheskiye Issledovaniya, Yakutsk, 1974 p167-175.